Norway to Iceland including the Faeroe Islands / compiled from the latest information in the Hydrographic Department - Great Britain. Hydrographic Office; Great Britain. Admiralty (Great Britain. Hydrographic Office, 1937)
Depths shown by soundings and isolines.Annotated in color to show principal lights."Large corrections . 18th June 1937."Includes notes and tables. Color 1:1,322,000